Alcohol, tobacco and others drugs: nursing academic´s perception - Laís Monteiro Araújo Campos Arêa Leão; Conceição de Maria Vaz Elias; Fernanda Matos Fernandes Castelo Branco; Claudete Ferreira de Souza Monteiro (Universidade Federal do Estado do Rio de Janeiro, 2014)
Objectives: To understand the perception of nursing students about alcohol, tobacco and other drugs in the context of their academic training. Method: This is a descriptive study with a qualitative approach using as production technique of the interview data with 15 nursing students of a private institution of higher education. Results: Data were grouped into two categories: knowledge of graduating nursing students on alcohol, tobacco and other drugs and academic formation versus practical application. Conclusion: The study shows a predominance of some participants' knowledge of drugs with specific information, without a more profound reflection on the subject in question on the politics of confrontation and actions of nurses.